Tailoring Thermal Transport Property of Graphene through Oxygen Functionalization - Zhang, Hengji; Fonseca, Alexandre F. [UNESP]; Cho, Kyeongjae (Amer Chemical Soc, 2014)
We compute thermal conductivity of graphene oxide at room temperature with molecular dynamics simulation. To validate our simulation model, we have investigated phonon scattering in graphene due to crystal boundary length and isotope defect, both of which are able to diagnose the behavior of long wavelength and short wavelength phonon scattering. Our simulation shows that thermal conductivity of pristine graphene has logarithmic divergence for the boundary length up to 2 pm. As compared with pristine graphene, thermal conductivity of graphene oxide can be reduced by a factor of 25 at low oxygen defect concentration. Moreover, we find that not only the concentration but also the configuration of the oxygen functional groups (e.g., hydroxyl, epoxide, and ether) has significant influence on the thermal conductivity. Through phonon mode analysis, phonon defect scattering as well as phonon localization are mainly responsible for the conspicuous reduced thermal conductivity. The simulation results have provided fundamental insight on how to precisely control thermal property of graphene oxide for thermal management and thermoelectric applications.